Strategy of continuous intake of vitamin K antagonists in the perioperative period of radiofrequency catheter ablation of atrial fibrillation - Suslina, Y.; Meshkova, M.; Doronin, A.; Rudenko, N. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The article analyzes first-hand experience of anticoagulation therapy in the perioperative period of catheter ablation of atrial fibrillation (AF). The group under study included 39 patients, who underwent 40 AF catheter ablations. For systemic anticoagulation all patients were taking vitamin K antagonists (with 37 patients taking Warfarin, one patient – Fenilin, and one – Sinkumar). Each patient was undergoing catheter ablation, with anticoagulant being taken continuously.